Allah Tritunggal dan Nilai Rumah Adat bagi Hidup Menggereja. Studi Kasus di Paroki Maria Diangkat ke Surga, Rejeng, Manggarai, Keuskupan Ruteng - Jegaut, Siprianus (Perspektif, 2021)
The focus in this study is “Triune God and the Value of Traditional House for Church Life in Manggarai.” It is a case study in the parish dedicated to the the Assumption of the Blessed Virgin Mary into Heaven, Rejeng, Ruteng Diocese.” The Church believes that God has already worked with in every culture wherever the Gospel is proclaimed. Proclamation of the gospel aims to contextualize it into the culture, in such a way that the gospel can truly be accepted in any culture. The Christian congregations do not only accept it but also live it out with in their culture. Their lives are truly imbued by the spirit of the gospel. This study aims to investigate how the faith of the people takes root in their culture. The method used in this study is a qualitative one with two approaches, namely literature review and interviews. This study finds out three main points: the communion with God; the traditional house as the place to share love; and the celebration of faith in community.